Natural Deep Eutectic Solvent (NADES) Extraction Improves Polyphenol Yield and Antioxidant Activity of Wild Thyme (Thymus serpyllum L.) Extracts - Pavlić, Branimir (2022)
Funding Information: info:eu-repo/grantAgreement/FCT/6817 - DCRRNI ID/UIDB%2F50006%2F2020/PT Funding: This research was supported by the Science Fund of the Republic of Serbia, 6060592, Natural Deep Eutectic Solvents for Green Agri-Food Solutions—DEStiny and 7750168, Novel extracts and bioactive compounds from under-utilized resources for high-value applications—BioUtilize. This project received funding from the European Union’s Horizon 2020—European Research Council (ERC)—under grant agreement No ERC-2016-CoG 725034. T Funding Information: This research was supported by the Science Fund of the Republic of Serbia, 6060592, Natural Deep Eutectic Solvents for Green Agri-Food Solutions?DEStiny and 7750168, Novel extracts and bioactive compounds from under-utilized resources for high-value applications?BioUtilize. This project received funding from the European Union?s Horizon 2020?European Research Council (ERC)?under grant agreement No ERC-2016-CoG 725034. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.